Exercise intensity governs tumor control in mice with breast cancer - Gomes-Santos, Igor L.; Kumar, Ashwin S.; Hausmann, Franziska; Meyer, Max N.; Shiferaw, Sarah Z.; Amoozgar, Zohreh; Jain, Rakesh K.; Fukumura, Dai (Frontiers in Immunology, 2024)
Introduction Exercise is recommended as an adjunct therapy in cancer, but its effectiveness varies. Our hypothesis is that the benefit depends on the exercise intensity. Methods We subjected mice to low intensity (Li), moderate intensity (Mi) or high intensity (Hi) exercise, or untrained control (Co) groups based on their individual maximal running capacity. Results We found that exercise intensity played a critical role in tumor control. Only Mi exercise delayed tumor growth and reduced tumor burden, whereas Li or Hi exercise failed to exert similar antitumor effects. While both Li and Mi exercise normalized the tumor vasculature, only Mi exercise increased tumor infiltrated CD8+ T cells, that also displayed enhanced effector function (higher proliferation and expression of CD69, INFγ, GzmB). Moreover, exercise induced an intensity-dependent mobilization of CD8+ T cells into the bloodstream. Conclusion These findings shed light on the intricate relationship between exercise intensity and cancer, with implications for personalized and optimal exercise prescriptions for tumor control.